Zinc-modulated Fe–Co Prussian blue analogues with well-controlled morphologies for the efficient sorption of cesium. Issue 7 (26th January 2017) - Liu, Jiayi; Li, Xuning; Rykov, Alexandre I.; Fan, Qiaohui; Xu, Wei; Cong, Weimin; Jin, Changzi; Tang, Hailian; Zhu, Kaixin; Ganeshraja, Ayyakannu Sundaram; Ge, Rile; Wang, Xiaodong; et al.
Abstract : Morphology-controllable KFe x Zn1− x [Co(CN)6 ] with different cesium uptake capacities were synthesized, based on which a Zn 2+ -modulated model was proposed. Abstract : Prussian blue analogues (PBAs) with tunable compositions and morphologies have demonstrated great potential in many applications. We successfully synthesized a series of KFe x Zn1− x [Co(CN)6 ] (Fe x Zn1− x –Co) PBAs with well-controlled compositions and morphologies and used them as adsorbents for the removal of Cs + ions. The increase of Zn : Fe ratio had a significant influence on the final morphology and improved the sorption capacity for Cs. X-ray diffraction and X-ray absorption fine structure spectra were used to confirm that the Cs + ions were inserted into the crystal channels rather than simply adsorbed on the surface of the PBAs. Based on the quantitative correlation between the concentration of ions released from the PBAs and the Cs + ions adsorbed, the mechanism of Cs + sorption in the Fe x Zn1− x –Co PBAs was studied and a Zn 2+ -modulated Cs + sorption model, which illustrated the difference in sorption behavior between the Fe x Zn1− x –Co PBAs, was proposed and confirmed by FTIR spectra, extended X-ray absorption fine structure spectra and 57 Fe Mössbauer spectra. The results indicated that the Fe x Zn1− x –Co PBAs are excellent candidates for the removal of radioactive 137 Cs from nuclear waste.